Risk of Spontaneous Abortion After Inadvertent Human Papillomavirus Vaccination in Pregnancy. Issue 1 (July 2018) - Kharbanda, Elyse O.; Vazquez-Benitez, Gabriela; Lipkind, Heather S.; Sheth, Sangini S.; Zhu, Jingyi; Naleway, Allison L.; Klein, Nicola P.; Hechter, Rulin; Daley, Matthew F.; Donahue, James G.; Jackson, Michael L.; Kawai, Alison Tse; et al.
Abstract : OBJECTIVE: To evaluate the risk of spontaneous abortion after quadrivalent human papillomavirus (4vHPV) vaccination before and during pregnancy across seven integrated health systems within the Vaccine Safety Datalink. METHODS: Within a retrospective observational cohort, we compared risks for spontaneous abortion after 4vHPV in three exposure windows: distal (16–22 weeks before the last menstrual period [LMP]), peripregnancy (within 6 weeks before the LMP), and during pregnancy (LMP through 19 weeks of gestation). Women 12–27 years of age with a pregnancy between 2008 and 2014, with continuous insurance enrollment 8 months before and through pregnancy end, and with a live birth, stillbirth, or spontaneous abortion were included. Pregnancies were identified through validated algorithms. Spontaneous abortions and stillbirths were verified by chart review with spontaneous abortions adjudicated by clinical experts. We excluded multiple gestations, spontaneous abortions before 6 weeks of gestation, and women using medications increasing risk of spontaneous abortion. Spontaneous abortion risk after 4vHPV during pregnancy was compared with distal vaccination using time-dependent covariate Cox models. Spontaneous abortion risk for peripregnancy compared with distal vaccination was evaluated with standard Cox models. RESULTS: We identified 2, 800 pregnancies with 4vHPV exposure in specified risk windows: 919 (33%) distal, 986 (35%) peripregnancy, and 895 (32%) during pregnancy. Mean age was 22.4 years in distal and peripregnancy groups compared with 21.4 years among women vaccinated during pregnancy. Among women with distal 4vHPV exposure, 96 (10.4%) experienced a spontaneous abortion. For peripregnancy and during pregnancy exposures, spontaneous abortions occurred in 110 (11.2%) and 77 (8.6%), respectively. The risk of spontaneous abortion was not increased among women who received 4vHPV during pregnancy (adjusted hazard ratio 1.10, 95% CI 0.81–1.51) or peripregnancy 1.07 (0.81–1.41). CONCLUSION: Inadvertent 4vHPV exposure during or peripregnancy was not significantly associated with an increased risk of spontaneous abortion. Abstract : Quadrivalent human papillomavirus vaccination inadvertently administered during pregnancy or peripregnancy is not associated with increased risk of spontaneous abortion.